KOMUNIKASI BISNIS DALAM PERSPEKTIF ISLAM - sifa hamama (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2017)
The purpose of this article is to construct the principles ofbusiness communication which is based the Qur’an. The author usedeductive approach to analyze this topic. The steps are: (1) looking forsome verses which are relevant, (2) analyzing the text, (3) analyzing thepresent context, and (4) making some conclusions. Specifically, theQur’an is not talking about the problem of business communication butthere are some verses that are explaining the principles ofcommunication as qaulan balighan, qaulan maisuran, qaulan kariman,qaulan ma’rufan, qaulan layyinan, qaulan saddidan, and qaulal-Zur.